2013
DOI: 10.3390/ijms140612367
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Role of GPR87 in Urothelial Carcinoma of the Bladder

Abstract: The orphan GPR87 has recently been matched with its ligand LPA, which is a lipid mediator with multiple physiological functions, including cancer cell proliferation. This study aimed to clarify the role of GPR87 in urothelial carcinoma of the bladder. GPR87 expression was assessed in seven human bladder cancer cell lines. A replication-deficient recombinant adenoviral vector expressing shRNA targeting GPR87 (Ad-shGPR87), was constructed. Gene silencing was carried out using Ad-shGPR87. Immunohistochemical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…Regarding the biological properties of GPR87 in NSCLC, the present study demonstrated that GPR87 expression was correlated with tumor proliferation. The Ki-67 proliferation index was significantly higher in GPR87-positive compared to that in GPR87-negative tumors, which was consistent with the findings of a recent study on bladder carcinoma (16). Furthermore, with the use of serial sections, the Ki-67 immunostaining pattern was found to be immunohistochemically identical to that of GPR87 in the majority of the tumor samples (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding the biological properties of GPR87 in NSCLC, the present study demonstrated that GPR87 expression was correlated with tumor proliferation. The Ki-67 proliferation index was significantly higher in GPR87-positive compared to that in GPR87-negative tumors, which was consistent with the findings of a recent study on bladder carcinoma (16). Furthermore, with the use of serial sections, the Ki-67 immunostaining pattern was found to be immunohistochemically identical to that of GPR87 in the majority of the tumor samples (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Another altered protein, GPR87, is a kind of cell‐surface molecule involved in signal transmission, and plays an essential role in tumor growth (Dorsam & Gutkind, ). Recent studies suggest that the association between GPR87 and tumorigenesis might be related to cancer cell proliferation (Okazoe et al, ; Zhang et al, ). Although the carcinogenic effect of AA was described in 1982, there is no study discussing the association between AA and GPR87 (Mengs, Lang, & Poch, ).…”
Section: Discussionmentioning
confidence: 99%
“…An adenoviral vector expressing shRNA expressed under the control of the RNA polymerase III-dependent promoter for supplying stable siRNA molecules was constructed as described previously [ 11 , 29 ]. A control adenoviral vector expressing shRNA against the scramble sequence of GPR87-siRNA (5′-UCUUAAUCGCGUAUAAGGCTT-3′) was also constructed (Ad-scramble).…”
Section: Methodsmentioning
confidence: 99%
“…Use of various mRNA expression databases, laser-capture-microdissected (LCM) tissue samples and immunohistochemistry with a panel of human tumors have demonstrated tumor-specific overexpression of GPR87 in many human cancers, including TCC [ 10 ]. Moreover, our recent clinical study of non-muscle-invasive bladder cancer also showed that GPR87-overexpression was correlated with higher tumor proliferation, and that patients with GPR87-positive tumors had a shorter intravesical recurrence-free survival period [ 11 ]. The precise molecular mechanisms by which GPR87 promotes cell proliferation and contributes to cell viability have not been sufficiently analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation